Pegadaian Digital Service - Ning Karnawijaya; Siti Rokhaniyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to determine the effect of Pegadaian Digital Service (PDS) on the financial inclusion of sharia business segments. The study was conducted using secondary data and analyzed by quantitative and qualitative methods. Quantitative method used the t-test to determine the significance of the effect of PDS on the financial inclusion of sharia business segments. The t-test was conducted two years before the release of PDS (2016-2017) and the two years after released of PDS (2018-2019). Sharia business segments in this study are sharia pawn bussiness (rahn) and micro fiducia sharia business (Arrum and Amanah). Furthermore, qualitative analysis is to find the right modeling for optimizing PDS in increasing financial inclusion in sharia business segments. The results showed that in the two years after the released of PDS the turnover, outstanding loan, and mu'nah revenue had a very significant increasing. There were strong correlations and significant differences in the achievement of turnover, outstanding loans, and mu’nah revenue between before and after the PDS, both in sharia pawn business (Rahn), Arrum and Amanah products. The results of empirical testing proved that PDS was supporting the acceleration of financial inclusion programs, especially in the sharia business segment at PT. Pegadaian. Optimizing PDS in increasing financial inclusion in sharia business segments can be done by developing a product based PDS optimization model.